Conceptualizations of Addiction and Moral Responsibility - Rise, Jostein; Halkjelsvik, Torleif (Frontiers in Psychology, 2019)
The present study explored the connection between conceptualizations of addiction and lay people’s inferences about moral responsibility. In Study 1, we investigated how natural variations in people’s views of addiction were related to judgments of responsibility in a nationwide sample of Norwegian adults. In Study 2, respondents recruited from Mechanical Turk were asked to consider different conceptualizations of addiction and report on how these would affect their judgments of moral responsibility. In Study 3, we tested whether manipulating conceptualizations through textual information and through the framing of addiction in terms of states versus behavior could influence participants’ judgments of moral responsibility. We found that attributions of moral responsibility were lower when addiction was connected to diseases and disorders, such as dysfunctional processes in the brain, and greater when addiction was associated with agency and addictive behaviors. In conclusion, different conceptualizations of addiction imply different moral judgments, and conceptualizations are malleable.